Exploring the Figurative Language through Confessional Discourse in Madeline Miller’s Circe - Muhammad Adi Reza (Language Horizon: Journal of Language Studies, 2025)
This study provides a qualitative analysis of Madeline Miller’s Circe, investigating the role of figurative language in the protagonist’s confessional inner monologues. Drawing on theories of figurative language (Perrine, 1982), confessional functions (Mandziuk, 2001), and confessional discourse (Mills, 1997), the research explores how these linguistic devices shape meaning and negotiate power. The findings show that devices like metaphor, simile, and personification and the like are integral to the therapeutic, didactic, and interrogatory functions of Circe’s self-revelations. They enable her to articulate complex internal struggles, process trauma, and question the patriarchal and divine systems that oppress her. The analysis highlights a recurring narrative pattern where Circe’s confessions map her journey from a position of marginalization and powerlessness toward one of significant agency and self-actualization. This transformation is marked by her evolving use of language to redefine her existence. The thesis concludes that figurative language is not merely ornamental but a fundamental tool for identity reconstruction. It is the primary vehicle through which Circe subverts her prescribed role, asserts her will, and achieves a powerful sense of selfhood independent of external validation.